2019
DOI: 10.1155/2019/1272897
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of the Accuracy of Cardiopulmonary Resuscitation Videos in English on YouTube according to the 2015 AHA Resuscitation Guidelines

Abstract: Over the last decade, YouTube has become one of the largest online resources for medical information. However, uploaded videos are published without any peer review or quality control, so incorrect and incomplete information can be easily disseminated via the virtual platform and can be perceived as correct. The YouTube website was searched for videos in English uploaded between 15 October 2015 and 21 October 2016 using the following keywords: “CPR,” “cardiopulmonary resuscitation,” and “basic life support.” T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
0
13

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(28 citation statements)
references
References 15 publications
1
14
0
13
Order By: Relevance
“…80 YouTube contains many videos about CPR education, but these videos provide insufficient information about BLS and advanced life support in adults and children according to current CPR guidelines. 81,82 In a systematic review of freely available mobile phone applications (Apps) giving instructions to perform adult CPR, only 15% adhered to current AHA or ERC guidelines. 83 Free open access medical education (FOAMed) is a dynamic collection of resources.…”
Section: Technology-enhanced Education To Teach Resuscitationmentioning
confidence: 99%
“…80 YouTube contains many videos about CPR education, but these videos provide insufficient information about BLS and advanced life support in adults and children according to current CPR guidelines. 81,82 In a systematic review of freely available mobile phone applications (Apps) giving instructions to perform adult CPR, only 15% adhered to current AHA or ERC guidelines. 83 Free open access medical education (FOAMed) is a dynamic collection of resources.…”
Section: Technology-enhanced Education To Teach Resuscitationmentioning
confidence: 99%
“…Among the remaining 18 studies, from which an average percentage of total possible QRT score could be computed or extracted, the average score was 44% with a range of 9%-71% (Figure 1). [10][11][12]14,[22][23][24]29,34,36,37,[39][40][41][42]44,47,48 The lowest mean score among studies that used internally validated QRTs was reported by Erdem and Karaca (10%), which used broad search criteria and videos from multiple author types. 23 Ferhatoglu et al, which also reported a low mean QRT score (13%), used a comprehensive QRT in which the authors analyzed each step of sleeve gastrectomy surgery.…”
Section: Video Content Qualitymentioning
confidence: 99%
“…Seven studies reported on the relationship between the video author type and scores on various QRTs (Figure 2). [22][23][24]36,39,40,42 Videos with authors classified as academic-physicians had higher internally validated QRT mean scores (46%) than those with authors classified as nonacademic-physicians or other (26%; P < .05, 95% confidence interval: 0.74-40.00). However, videos with authors classified as academic-physicians also had a wide range in QRT scores (range: 25%-75%).…”
Section: Relationship Of Video Author Type To Quality Ratingmentioning
confidence: 99%
“…YouTube enthält viele Videos zum CPR-Unterricht. Die Videos bieten jedoch nur unzureichende Informationen über BLS und erweiterte lebensrettende Maßnahmen für Erwachsene und Kinder auf Basis der aktuellen Leitlinien [ 82 , 83 ]. In einer systematischen Übersichtsarbeit zu frei verfügbaren Apps zur Anleitung von Reanimationsmaßnahmen bei Erwachsenen, basierten nur 15 % auf den aktuellen AHA- oder ERC-Leitlinien [ 84 ].…”
Section: Evidenzbasierte Leitlinienunclassified